2022
DOI: 10.1186/s12884-022-04895-6
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric violence and associated factors among women during facility based childbirth at Gedeo Zone, South Ethiopia

Abstract: Introduction Obstetric violence is a specific form of violence against women that violates their human rights. Conducted by obstetric care providers regarding the body and reproductive processes of the woman, being characterized by dehumanized assistance, abuse of interventionist actions, medicalization, and reversion of the process from natural to pathological. Objective To assess the magnitude of obstetric violence and associated factors among wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
10
1
2
Order By: Relevance
“…In general, facing labor complications was significantly associated with D&A care 28 . All these poor obstetric outcomes and patients' experiences could have indirectly led to increased maternal morbidity and mortality by promoting home deliveries rather than institutional delivery 29 …”
Section: Resultsmentioning
confidence: 99%
“…In general, facing labor complications was significantly associated with D&A care 28 . All these poor obstetric outcomes and patients' experiences could have indirectly led to increased maternal morbidity and mortality by promoting home deliveries rather than institutional delivery 29 …”
Section: Resultsmentioning
confidence: 99%
“…The current study revealed that 63% of mothers experienced physical or verbal abuse, 81.8% felt discomfort during care, and 54% received undignified care. In comparison, a study performed in another region indicated that 40.5% of women received non-dignified care, 22.2% reported abuses, and 30.1% reported inappropriate cultural consideration [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a 2017 study conducted across four regions of Ethiopia in various healthcare facilities, it was found that 36% of women had experienced at least one form of mistreatment during childbirth [ 19 ]. Nevertheless, recent reports have indicated that the prevalence of obstetric violence among Ethiopian mothers spans from 76.1 to 98.9% [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the tolerance level of the mother or her family exceeds the tolerance level, they often release their negative emotions on the nurses, such as loud reprimands and roars (particularly the nurses involved in obstetric violence), leading to the occurrence of WPV. Research shows that obstetric violence is associated with nurse burnout, bonuses, and a lack of educational opportunities [ 31 ]. Managers can take steps to reduce and prevent obstetric workplace violence.…”
Section: Discussionmentioning
confidence: 99%